ANALISIS PROSES PENGAMBILAN KEPUTUSAN DAN KEPUASAN KONSUMEN PRODUK PROGRAM AGRIBISNIS TAMAN TEKNOLOGI PERTANIAN (TTP) CIGOMBONG, KABUPATEN BOGOR - Puspita Sari, Dara; Ismail, Ahyar; Burhanuddin, Burhanuddin (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
The agribusiness program is one of the Cigombong TTP programs that can help assisted farmers and breeders and partners market their products at a better price. This study aims (1) to analyze the consumer decision-making process for the Cigombong TTP agribusiness program and (2) to analyze the consumer satisfaction of the Cigombong TTP agribusiness program product. The method used is descriptive analysis, Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results showed that the decision-making process of most consumers of the TTP Cigombong agribusiness program was motivated to get quality products, sought information from family or friends, the most interesting promotions were product quality, considering product purchases as needed, making planned purchases regularly every week. once and expressed satisfaction after purchasing the TTP Cigombong agribusiness program product. Based on CSI analysis, consumers are satisfied with the performance of the TTP Cigombong agribusiness program with a value of 79.19% and the priority attributes to be repaired according to the IPA matrix are the attributes of security assurance or product certification.